Reforming the Fund's Policy on Non-Toleration of Arrears to Official Creditors. (Policy Papers; Policy Paper ;, 2015)
Background: As a follow-up to the May 2013 Executive Board's discussion of the paper on Sovereign Debt Restructuring: Recent Developments and Implications for the Fund's Legal and Policy Framework (hereinafter, the '2013 Paper'), this paper proposes a reform to the Fund's policy on non-toleration of arrears owed to official bilateral creditors ('NTP') with a view to addressing the major issues related to official sector involvement (OSI) discussed in the 2013 Paper. Unlike the Fund's lending-into-arrears ('LIA') policy for private creditors, the NTP prevents Fund lending to countries if they owe unresolved arrears to official bilateral creditors, unless the arrears are covered by a Paris Club agreement or the creditor consents to the Fund providing financing. Nature of the problem: As staff foreshadowed in the 2013 Paper, several aspects of the current NTP present challenges in a changing and increasingly diverse landscape for official bilateral finance. For example, the NTP's reliance on the practices and conventions of the Paris Club creates challenges in an environment where a growing number of creditors are non-Paris Club members. In particular, the NTP's dependence on the Paris Club's comparability of treatment principle to deem away arrears to non-Paris Club bilateral creditors is difficult to justify in circumstances where a Paris Club agreement is not sufficiently representative and the bulk of official bilateral claims are held by non-Paris Club creditors. Further, where there is no Paris Club agreement, the current policy can give individual official bilateral creditors a veto over Fund lending decisions, drawing no distinction between creditors that are contributing to the financing requirements of the program and those that are not, thus leaving the system vulnerable to holdouts. Proposed modification: Staff's proposal envisages a two-step process: in the first step, all creditors would be encouraged to reach a consensus. While the Paris Club is currently a well-established forum for OSI, the Fund would also recognize agreements among creditors reached in other representative fora, should such fora emerge. If an agreement is reached through the Paris Club and the creditor group so formed represents a significant portion of total official bilateral claims, the Fund would rely on its current practices and deem away arrears to nonparticipating creditors based on the Club's comparability of treatment principle. Only when an agreement cannot be reached (i) with a representative group of creditors in the Paris Club, or (ii) with each creditor in an alternative grouping or bilaterally, would the Fund consider lending into arrears owed to official bilateral creditors in carefully circumscribed circumstances. The decision to lend in these situations would be subject to a need for prompt Fund assistance, an assessment that the debtor is making good faith efforts to reach an agreement and that the absence of a debt restructuring is due to the unwillingness of the creditor to reach an agreement consistent with the parameters of the Fund-supported program, and a judgment on whether the decision to lend could negatively affect the Fund's ability to mobilize official financing packages in the future. Likely impact: Staff's proposal will strengthen incentives for collective action among official bilateral creditors in situations where OSI is necessary. The two-step process encourages individual official bilateral creditors to be part of a multilateral agreement, thus reducing the risk that the Fund would be prevented from assisting a member in need because certain official bilateral creditors are seeking more favorable treatment of their claims at the expense of other contributing creditors. Importantly, the policy will continue to protect official bilateral creditors, as any decision to lend into arrears will be subject to the debtor's good faith efforts, will be applied in a way that preserves the Fund's ability to mobilize official financing packages in future, and be subject to the Board's approval. Next steps: If the Board supports the proposed modification, the new policy will apply immediately to all future Fund disbursements (including under existing arrangements) with respect to existing and future arrears owed to official bilateral creditors.